Nigeria's exports : problems, prospects, and implications for economic growth - Lewis, A. Olufemi (Budapest : Center for Afro-Asian Research of the Hungarian Academy of Sciences, 1973)
The purpose of this paper is to analyse the problems and prospects of Nigeria's exports and to indicate the implications of the analysis for the country's economic growth.
Includes bibliographical references.
osc 07/03/2019
Arch
Keywords: Exports; Economic conditions; Trade; Economic growth- Nigeria; Nigeria